1995
DOI: 10.1111/j.1365-294x.1995.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative genetic structure of a population of Rhizobium meliloti isolated directly from soil and from nodules of alfalfa (Medicago sativa) and sweet clover (Melilotus alba)

Abstract: Insertion sequence (IS) hybridization was used to define the structure of a population of Rhirobium meliloti isolated directly from soil and from nodules of Medicago sativn (alfalfa) and Melilotus alba (sweet clover) grown under controlled conditions and inoculated with a suspension of the same soil. The detection of R. meliloti isolated from soil on agar plates was facilitated by use of a highly species specific DNA probe derived from ISRm5. All R. meliloti o'btained directly from soil proved to be symbiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
3
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 22 publications
(11 reference statements)
2
43
3
2
Order By: Relevance
“…Both fava bean and pea plants are able to discriminate among the diversity of rhizobial genotypes that are present in soil. Similar results were reported previously for other legumes (6,16,51). Furthermore, relatively small differences in frequencies of R. leguminosarum bv.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both fava bean and pea plants are able to discriminate among the diversity of rhizobial genotypes that are present in soil. Similar results were reported previously for other legumes (6,16,51). Furthermore, relatively small differences in frequencies of R. leguminosarum bv.…”
Section: Discussionsupporting
confidence: 81%
“…Dominance of particular rhizobial genotypes in nodules may result from a higher abundance in soil rather than a greater nodulation competitiveness, as shown for certain genotypes within Sinorhizobium meliloti indigenous populations (6,16,43). This may explain the finding that nodule-dominant genotypes from soil populations do not necessarily show superior competitiveness for nodulation compared to minor occupants when evaluated under nonsoil conditions (7,27,31).…”
mentioning
confidence: 53%
“…En este sentido, la clasificación propuesta por Jordan en 1984, no indicó formas extremas o intermedias, probablemente debido al muestreo reducido de leguminosas, el cual no fue representativo de la población total (Martí-nez-Romero & Caballero-Mellado 1996). Por lo tanto, se ha señalado la inconveniencia de tomar en cuenta sólo los aislamientos nodulares, porque se pasa por alto la gran diversidad de los grupos de rizobios existentes en el suelo (Bromfield et al 1995), además, se conoce la existencia de un grupo de rizobios no simbióti-cos presentes en él (Sullivan et al 1996). Este criterio es relativo y subjetivo (Bécquer et al 2000), puesto que va a depender en parte de las condiciones del medio de cultivo, las cuales son: composición, pH, temperatura y origen de la cepa, sean provenientes de un aislamiento nodular o de repiques frecuentes de cepas ya aisladas y conservadas en el laboratorio, factores que modifican la velocidad de crecimiento.…”
Section: Discussionunclassified
“…There may be differences between the population densities of different strains in soil and these differences may infl uence the outcome of nodulation. Dominance of a particular rhizobial strain in nodules may result from its higher abundance in soil as reported in Ensifer meliloti indigenous for a population [11][12][13] or may not be correlated [14][15][16]. Use of three predominant strains as inoculants showed that one strain formed majority of the nodules while the other two were minor occupants in the nodules.…”
Section: Introductionmentioning
confidence: 99%